Suferințele tânărului Ghica - Nicolae Mecu (Revista de Istorie și Teorie Literară)
The subject of this presentation consists of three very little known works of the writer, economist and Liberal ideologist Ion Ghica (1816–1897), from 1835, 1838 and 1853, therefore, at least the first two ones written in his early youth. Conceived and written in French and addressed to the great European powers, first and foremost to France and England, they are meant to inform the West on Russia’s expansionist targets and on the dangers represented by this expansion to the European South-East for the West. Presenting briefly their contents of political history, the study emphasizes the literary component of the discourse, revealing the parts that identify the anticipations of the future Realist narrator, eager for facts and colour, creator of memorable scenes and characters.